The effect of high-intensity rowing and combined strength and endurance training on left ventricular systolic function and morphology - duManoir, G. R.; Haykowsky, M. J.; Syrotuik, D. G.; Taylor, D. A.; Bell, G. J. (International Journal of Sports Medicine, 2007)
Combined strength and endurance training may result in alterations in left ventricular (LV) systolic function and morphology, however, the acute effect of high-intensity rowing exercise and concurrent training-induced adaptations on LV systolic function are not well known. The purpose of this investigation was to assess LV systolic function before and after a simulated 2000-m rowing race on a Concept II rowing ergometer and evaluate these adaptations following 10 weeks of concurrent strength and endurance training. Furthermore, resting LV morphology was assessed prior to and following the 10-week training program. Ten male subjects underwent two-dimensional echocardiograms at rest, immediately following (95 ± 27 s), as well as 5 and 45 minutes after, a simulated 2000-m rowing race. These measurements were also made before and after 10 weeks of training. Irrespective of testing time, performance of a 2000-m rowing race resulted in an increase in fractional area change (0.51 ± 0.06 vs. 0.63 ± 0.09; p < 0.05) due to an increase in LV contractility. Concurrent strength and endurance training resulted in an increase in the resting LV diastolic cavity area (20.64 ± 2.59 vs. 22.82 ± 2.17 cm2; p < 0.05), end systolic myocardial area (23.27 ± 4.86 vs. 24.56 ± 4.00 cm2; p < 0.05) and LV mass (179.07 ± 46.91 g vs. 210.46 ± 51.13 g; p < 0.05). These findings suggest that the acute increase in LV systolic function following a simulated 2000-m rowing race was due to heightened LV contractile reserve. Further, 10 weeks of combined strength and endurance training resulted in an increase in resting LV diastolic cavity size, wall thickness and mass.